DNMT1 is predictive of survival and associated with Ki-67 expression in R-CHOP-treated diffuse large B-cell lymphomas - Loo, SK; Ch'ng, ES; Lawrie, CH; Muruzabal, MA; Gaafar, A; Pomposo, MP; Husin, A; Salleh, MS; Banham, AH; Pedersen, LM; Møller, MB; Green, TM; et al. (Elsevier, 2017)
DNMT1 is a target of approved anti-cancer drugs including decitabine. However, the prognostic value of DNMT1 protein expression in R-CHOP-treated diffuse large B-cell lymphomas (DLBCLs) remains unexplored. Here we showed that DNMT1 was expressed in the majority of DLBCL cases (n = 209/230, 90.9%) with higher expression in germinal centre B-cell-like (GCB)-DLBCL subtype. Low and negative DNMT1 expression (20% cut-off, n = 33/230, 14.3%) was predictive of worse overall survival (OS; p < 0.001) and progression-free survival (PFS; p < 0.001). Nonetheless, of the 209 DNMT1 positive patients, 33% and 42% did not achieve 5-year OS and PFS, respectively, indicating that DNMT1 positive patients showed considerably heterogeneous outcomes. Moreover, DNMT1 was frequently expressed in mitotic cells and significantly correlated with Ki-67 or BCL6 expression (r = 0.60 or 0.44, respectively; p < 0.001). We demonstrate that DNMT1 is predictive of DLBCL patients' survival, and suggest that DNMT1 could be a DLBCL therapeutic target due to its significant association with Ki-67.